ADAPTASI SPASIAL PADA RUMAH DOME NGELEPEN SUMBERHARJO, PRAMBANAN, SLEMAN - Priasmara Putra Marindrha (Universitas Negeri Yogyakarta, 2018)
ABSTRACTThe aim of this research is to know spatial adaptation of dome house of Ngelepen, Prambanan, Sleman, Yogyakarta which originally lived in Java traditional house, then moved to dome house which has different building characteristic in Java. The addition of outdoor space that occurred in Ngelepen dome provides an indication of the existence of the spatial adaptation of the living environment and human life. This research uses qualitative-rationalistic method approach. The results of this study led to the formation of spatial adaptation that occurred in the dome house Ngelepen is a functional adaptation to the needs of existing space. The adoption of functional adaptation by residents is the addition of outdoor space which includes the addition of new functions, the direction of adding new space, and the extent of the addition of function space. The social and economic aspects are the factors that influence the increase of space outside the dome house because of the change of status from the agrarian environment into the dome tourist village causing the increasing economic and social needs of the inhabitants. Keywords: Functional, Ngelepen dome, Spatial adaptation, Space addition. ABSTRAKTujuan Kajian ini adalah untuk mengetahui adaptasi spasial rumah dome Ngelepen, Prambanan, Sleman, Yogyakarta yang semula tinggal di rumah adat Jawa, kemudian pindah ke rumah kubah yang memiliki karakteristik bangunan berbeda di pulau Jawa. Penambahan ruang luar yang terjadi di Ngelepen dome memberikan indikasi adaptasi spasial lingkungan dan kehidupan manusia. Kajian ini menggunakan pendekatan metode kualitatif-rasionalistik. Hasil Kajian ini menunjukkan bahwa bentuk adaptasi spasial yang terjadi di rumah dome Ngelepen merupakan adaptasi fungsional terhadap kebutuhan ruang yang ada. Penerapan adaptasi fungsional oleh penghuni adalah penambahan ruang di luar rumah yang meliputi penambahan fungsi baru, arah penambahan ruang baru, dan luasan penambahan fungsi ruang. Aspek sosial dan ekonomi adalah faktor-faktor yang mempengaruhi pertambahan ruang di luar rumah dome karena perubahan status dari lingkungan agraris ke desa wisata dome yang menyebabkan meningkatnya kebutuhan ekonomi dan sosial penghuni.Kata kunci: Fungsional, Dome Ngelepen, Adaptasi spasial, Penambahan ruang.